Teachers and the Factors Shaping Qur’anic Reading Proficiency at MTs Darul Hasanah Kutacane, Aceh - Jurnalisma Sujariwa (Yayasan Bayt Shufiya Nusantara, 2023)
This study aims to test the effectiveness of efforts made by schools and teachers in improving students' ability to read the Qur'an in accordance with the rules of tajwid. This study uses a quantitative approach with a survey method, where primary data is collected through the distribution of questionnaires to 36 students and strengthened by the results of interviews with teachers and principals. The test results showed that most of the students had good ability to read the Quran, and the questionnaire instruments used had met the validity and reliability requirements with a Cronbach's Alpha value of 0.88. These findings show that the improvement of the ability to read the Qur'an correctly according to tajweed is influenced by the synergy between teachers, students, and school support. In addition, school principals also play a role through the addition of additional tutoring programs and the improvement of learning facilities and infrastructure that support Qur'anic literacy activities.